Studi Histopatologi Limpa Anjing Penderita Distemper Dikaitkan Dengan Sebaran Sel-Sel Radang Pada Otak Dan Paru (HISTOPHATOLOGICAL STUDY OF SPLEEN ON DOGS INFECTED WITH DISTEMPER ASSOCIATED TO INFLAMATION IN THE BRAIN AND LUNGS) - Fadilah, Muhamad Furkam; Berata, I Ketut; Kardena, I Made (Buletin Veteriner Udayana, 2015)
This study aim was to determine the distribution of inflammatory cells in canine distemper in terms of the level of inflammation in the spleen, brain and lungs. The sample used 20 infected dogs wihich from the spleens, brains, and lungs of the dogs were collected. These organs were processed for histophatological observation using harris hematoxilyn-eosyn stain. The inflammation of the organs examined by using binocular microscope with 200X magnification. the results showed that inflammation was observed in the spleens: 9 samples (45%) showed the presence of lymphoidcells that experienced a mild inflammation 7 (35%) moderate inflammation, and 4 (20%) severe inflammation in brain, 3 samples (15%) did not show observe inflammation, 12 (60%) mild, 5(25%) moderate inflammation, and not observed any severe inflammation in brain, pulmonary: 6(30%) mild inflammation, 11 (55%) moderate inflammation, and 3 (15%) severe inflammation. It can be concluded that the inflammation was observed microscopically in the spleen, brain and lungin the dog that infected with canine distemper virus
Keywords: histopathology; distemper; spleen; brain; lungs